2019
DOI: 10.1051/epjconf/201920609004
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency in pseudorapidity space of pp collisions at √s $ \sqrt s $ = 7 TeV

Abstract: The intermittency-type fluctuations in the pseudorapidity space of pp collisions at $ \sqrt s $ = 7 TeV done at the LHC is investigated, by analysing the scaling properties (exponents) of the factorial moments of the event multiplicity distributions in decreasing pseudorapidity bin size. It is found that the scaling behaviour persists in the $ \sqrt s $ = 7 TeV regime, indicating intermittent behaviour as observed previously in analyses done at lower energies [1,2]. Comparison is also made with the theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…With the LHC at CERN ushering in a new era of TeV-scale high energy physics, it is worthwhile to reinvestigate this phenomenon in a new energy regime. In our previous work [3], we found that intermittent phenomenon exists in pp collisions at s = 7 TeV. That motivates our current investigation, where the analysis is extended to include the other available energies in Run 1 from the CERN Open Data Portal -0.9 and 8 TeV from the CMS collaboration.…”
Section: Motivation and Objectivesmentioning
confidence: 59%
“…With the LHC at CERN ushering in a new era of TeV-scale high energy physics, it is worthwhile to reinvestigate this phenomenon in a new energy regime. In our previous work [3], we found that intermittent phenomenon exists in pp collisions at s = 7 TeV. That motivates our current investigation, where the analysis is extended to include the other available energies in Run 1 from the CERN Open Data Portal -0.9 and 8 TeV from the CMS collaboration.…”
Section: Motivation and Objectivesmentioning
confidence: 59%
“…For examples of past analyses using these datasets, see e.g. [123,[167][168][169][170][171][172][173][174][175][176][177].…”
Section: Jhep07(2022)146mentioning
confidence: 99%
“…For examples of past analyses using these datasets, see e.g. [123,[167][168][169][170][171][172][173][174][175][176][177].…”
Section: Celestial Non-gaussianities In Cms Open Datamentioning
confidence: 99%